Investigating Figurative Language in “Lose You to Love Me” Song Lyric - Erniyanti Nur Fatahhela Dewi; Didin Nuruddin Hidayat; Alek Alek (English Education Department, 2020)
Figurative language is part of the semantic aspect in language that employs various figures in a language. The study discussed an analysis of the figurative languages in the Selena Gomez song. The study aimed at finding out the kind and the meaning of figurative languages in her song “Lose You to Love Me”. The source of the data was taken from the lyrics of Selena Gomez’s song. Her song was classified as a pop song released on 23rd October 2019. In this analysis, the descriptive qualitative model was used with a pure structuralism approach, such as hyperbole, irony, paradox, personification, repetition, and simile. Then the types of figurative language were classified and analyzed. The result showed that six kinds of figurative languages were found: hyperbole 33.3%, Irony 11.1%, paradox 22.3%, personification 11.1%, repetition 11.1%, and simile 11.1%. The figurative language dominant is hyperbole since song lyrics are distorted by adding original meanings to explicit words. Instead, song lyrics contain a comparative meaning between denotative interpretation and connotative meaning. In addition, this song provides the essence of the song on aesthetic principles and colors.